Successful Integration of Hepatitis C Virus Point-of-Care Tests into the Denver Metro Health Clinic - A. Jewett; A. A. Al-Tayyib; L. Ginnett; B. D. Smith (AIDS Research and Treatment)
Background. The Centers for Disease Control and Prevention (CDC) recommends testing and linkage to care for persons most likely infected with hepatitis C virus (HCV), including persons with human immunodeficiency virus. We explored facilitators and barriers to integrating HCV point-of-care (POC) testing into standard operations at an urban STD clinic. Methods. The OraQuick HCV rapid antibody test was integrated at the Denver Metro Health Clinic (DMHC). All clients with at least one risk factor were offered the POC test. Research staff conducted interviews with clients (three HCV positive and nine HCV negative). Focus groups were conducted with triage staff, providers, and linkage-to-care counselors. Results. Clients were pleased with the ease of use and rapid return of results from the HCV POC test. Integrating the test into this setting required more time but was not overly burdensome. While counseling messages were clear to staff, clients retained little knowledge of hepatitis C infection or factors related to risk. Barriers to integrating the HCV POC test into clinic operations were loss to follow-up and access to care. Conclusion. DMHC successfully integrated HCV POC testing and piloted a HCV linkage-to-care program. Providing testing opportunities at STD clinics could increase identification of persons with HCV infection.